Online Communities and Online Activities of Politicians – Opinions of Internet Users - Jakubowski, Jakub; Olejnik, Iwona (My University, 2015)
: Marketing activity in the field of social media has seemed to be more professional for few years. This communication channel (web 2.0) is established and frequently used on the market of products and services. Social media services are also in progress. They are focused of big data, sale support or profiling offers at an angle of brand fan`s behavior in social media. Collaterally, similar activities in the field of politics appear. The objective of this article is answering the question: what is the attitude of the Internet users to promotion activities like this? It seems to be important from the effective and specific point of view in political communication of social media. Thus, we conducted research described in this text that is going to verify if social media services are the source of knowledge about politics in Poland. What is more, we wanted to check in which way the Internet users find information about politics and what is their level of engagement `around` politicians` online activity.
Keywords: the Internet; web 2.0; new media; virtual communities; political communication